Immunomodulatory Effects of Flavonoids: Possible Induction of T CD4+ Regulatory Cells Through Suppression of mTOR Pathway Signaling Activity - Hosseinzade, Aysooda; Sadeghi, Omid; Naghdipour Biregani, Akram; Soukhtehzari, Sepideh; Brandt, Gabriel S.; Esmaillzadeh, Ahmad (Frontiers in Immunology, 2019)
The increasing rate of autoimmune disorders and cancer in recent years has been a controversial issue in all aspects of prevention, diagnosis, prognosis and treatment. Among dietary factors, flavonoids have specific immunomodulatory effects that might be of importance to several cancers. Over different types of immune cells, T lymphocytes play a critical role in protecting the immune system as well as in the pathogenesis of specific autoimmune diseases. One of the important mediators of metabolism and immune system is mTOR, especially in T lymphocytes. In the current review, we assessed the effects of flavonoids on the immune system and then their impact on the mTOR pathway. Flavonoids can suppress mTOR activity and are consequently able to induce the T regulatory subset.